THE EFFECT OF CHITOSAN CONCENTRATION AND STORAGE TIME ON THE QUALITY OF SALTED-DRIED ANCHOVY (Stolephorus heterolobus) - Tri Winarni Agustini; Sri Sedjati (JOURNAL OF COASTAL DEVELOPMENT, 2007)
The use of chitosan as preservative agent in fish processing had been conducted for some reasons for example its usage as food additive that can prevent microbial growth, as antioxidative agent, and, to some extent to produce safe food. This research studied the application of chitosan on salted-dried anchovy (S. heterolobus) preservation during storage at room temperature. The aims of this research were to know the effect of treatment (chitosan concentration and storage time) on the quality of salted-dried anchovy (bacterial count and organoleptic test). The experimental design used was Split plot in time design and using Randomized Complete Block with two factors. The first factor was chitosan concentrations (0,0%; 0,5%; 1,0%) while the second factor storage time (0; 2; 4; 6; 8 weeks). The results indicated that chitosan concentration and storage time significantly reduced the total bacterial count (p<0,01) but not significantly different (p>0,05) for organoleptic test. The interaction of chitosan concentration and storage time significantly influenced the total bacterial count (p<0,01).